A report on a rare case of Kearns Sayre-like syndrome - Gupta, Y; Gupta, M; Sambhav, K; Phougat, A; Varshney, A (Nepalese Journal of Ophthalmology, 2010)
Purpose: To report the presentation of a rare case of Kearns-Sayre-like syndrome (KSS) Case: A 14-year-old boy presented with progressive drooping of both upper eyelids for 10 years. Past history of right sided hemi-plegia and left facial nerve palsy was present. Examination (OU) showed total external ophthalmoplegia, ptosis and pigmentary retinopathy. The patient also had a short stature (height 121.9 cm) for his age. Keywords: Kearns Sayre syndrome; total external ophthalmoplegia; ptosis DOI: 10.3126/nepjoph.v2i2.3725 Nep J Oph 2010;2(2) 160-163